Work force planning in the printing industry - Martin Mundschenk; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2005)
Effectiveness in the use of the work force is often the crucial advantage in a company's long-term success over its competitors, especially in technology driven and highly competitive branches as the one considered in this article. While employee scheduling and rostering has been the topic of extensive research over the past decades, usually it is assumed that the size of the work force is either given or can be obtained without difficulty. In this research we provide an integer programming model for long-term staffing decisions. The model is based on qualification profiles, the number of which grows exponentially in terms of the number of processes considered. We present empirical results for a company from the printing branch which show the potential of our approach. In particular, it will be shown that applying the model lowers the total cost of the work force in the range of 26% - 39%.
Keywords: 650; Work force planning; qualification profile; printing company; empirical results; Personaleinsatzplanung; Ganzzahlige Optimierung; Qualifikation; Druckindustrie; Theorie; Deutschland